Pemasangan Arrester Multi Chamber Untuk Mengatasi Gangguan Surja Petir di Penyulang Pecatu - Perdana, I Gede Gerry Julius; Arjana, I Gede Dyana; Wijaya, I Wayan Arta (Majalah Ilmiah Teknologi Elektro, 2018)
Pecatu feeder is a feeder that has a radial distribution system configuration, the length of the line is 31 kms . In addition, these feeders have as many as 105 pieces of distribution transformers with a total number of subscribers reached 11,800 subscribers. To protect the feeder from lightning surge interference, then Arrester Multi Chamber are installed on each goalpost to the distribution network to protect the distribution channel in Pecatu feeder. This research is an analisys about installation of Multi Chamber Arrester ini Pecatu Feeder with purpose,  how to knows about technical data and performance from Installation of Multi Chamber Arrester at along of distrubtion line of Pecatu Feeder and knows the disturbance data caused by the lightning strike. By placing the arrester approximately 200 meters in every four to five poles , Obtained a voltage increase when experiencing lightning surge with wave speed 4/10 ?s, with time to peak 10 ?s . Whereas with a 65 kA current flow of 4,147.1831 kV, while for a 20 kA surge current with a placement of arresters on each distribution line, the wave velocity and the time to the same peak are 713,385827 kV.